2003
DOI: 10.1128/mcb.23.4.1260-1268.2003
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the Nuclear Receptor Coactivator RAP250 in Mice Results in Placental Vascular Dysfunction

Abstract: Coactivators constitute a diverse group of proteins that are essential for optimal transcriptional activity of nuclear receptors. In the past few years many coactivators have been identified but it is still unclear whether these proteins interact indiscriminately with all nuclear receptors and whether there is some redundancy in their functions. We have previously cloned and characterized RAP250 (ASC-2/PRIP/TRBP/NRC), an LXXLLcontaining coactivator for nuclear receptors. In order to study its biological role, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
89
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 45 publications
3
89
1
Order By: Relevance
“…We and others have shown that inactivation of both of the AIB3 alleles in mice results in embryonic lethality due to defects in placental, cardiac, and hepatic development (23)(24)(25). These phenotypes are similar to those encountered in mice lacking PPAR␥ or PPAR␥-binding protein (26,27).…”
Section: Introductionmentioning
confidence: 49%
“…We and others have shown that inactivation of both of the AIB3 alleles in mice results in embryonic lethality due to defects in placental, cardiac, and hepatic development (23)(24)(25). These phenotypes are similar to those encountered in mice lacking PPAR␥ or PPAR␥-binding protein (26,27).…”
Section: Introductionmentioning
confidence: 49%
“…TRBP stimulates nuclear receptor-mediated gene activation and interacts with multiple components of the transcription complex. Genetic deletion of TRBP in mice is embryonically lethal, with severe defects in embryonic development (Kuang et al, 2002;Antonson et al, 2003). CoAA has been shown to synergistically activate transcription with TRBP and participate in the regulation of alternative splicing decisions (Auboeuf et al, 2004(Auboeuf et al, , 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to NRs, NRC also activates a variety of other transcription factors, such as c-Fos and c-Jun (31,34,40,41). Mice null for expression of NRC have been recently reported by three different laboratories (2,32,73). Deletion of the NRC gene in mice revealed that null mutants (NRC Ϫ/Ϫ ) die during early stages of embryogenesis (9.75 to 13.5 dpc) while mice heterozygous for the NRC gene (NRC ϩ/Ϫ ) in a mixed genetic background (C57/129) appear to be normal in growth and development.…”
mentioning
confidence: 99%
“…The following findings summarize these results. CBP Ϫ/Ϫ , p300 Ϫ/Ϫ , TRAP220 Ϫ/Ϫ , and NRC Ϫ/Ϫ mice are embryonic lethal (2,20,26,32,33,57,68,73). TRAP220 ϩ/Ϫ mice are viable but exhibit pituitary hypothyroidism.…”
mentioning
confidence: 99%
See 1 more Smart Citation